E7766, a Macrocycle‐Bridged Stimulator of Interferon Genes (STING) Agonist with Potent Pan‐Genotypic Activity. (25th February 2021) - Kim, Dae‐Shik; Endo, Atsushi; Fang, Francis G.; Huang, Kuan‐Chun; Bao, Xingfeng; Choi, Hyeong‐wook; Majumder, Utpal; Shen, Young Y.; Mathieu, Steven; Zhu, Xiaojie; Sanders, Kristen; Noland, Thomas; et al.
Abstract: A strategy for creating potent and pan‐genotypic stimulator of interferon genes (STING) agonists is described. Locking a bioactive U‐shaped conformation of cyclic dinucleotides by introducing a transannular macrocyclic bridge between the nucleic acid bases leads to a topologically novel macrocycle‐bridged STING agonist (MBSA). In addition to substantially enhanced potency, the newly designed MBSAs, exemplified by clinical candidate E7766, exhibit broad pan‐genotypic activity in all major human STING variants. E7766 is shown to have potent antitumor activity with long lasting immune memory response in a mouse liver metastatic tumor model. Two complementary stereoselective synthetic routes to E7766 are also described. Abstract : Locking the bioactive conformation of cyclic dinucleotides led to a new class of stimulator of interferon gene (STING) agonists, macrocycle bridged STING agonists (MBSA), exemplified by E7766 . Having entropic advantage upon binding STING proteins, E7766 exhibits enhanced potency and pan‐genotypic activity.